Modulation of Immune Response by RAGE and TLR4 Signalling in PBMCs of Diabetic and Non-Diabetic Patients - Frasnelli, Sabrina Cruz Tfaile [UNESP]; Medeiros, Marcell Costa de [UNESP]; Bastos, Alliny de Souza [UNESP]; Costa, D. L.; Orrico, Silvana Regina Perez [UNESP]; Rossa Júnior, Carlos [UNESP] (Wiley, 2015)
Diabetes is associated with increased glucose levels and accumulation of glycated products. It is also associated with impairment in the immune response, such as increased susceptibility to infections. In this study, we assessed the possible interactions between TLR4 and RAGE signalling on apoptosis and on the expression of inflammatory cytokines in PBMC from individuals with and without diabetes. PBMCs were isolated from seven diabetic patients and six individuals without diabetes and stimulated in vitro with bacterial LPS (1 μg/ml) associated or not with BSA-AGE (200 μg/ml). This stimulation was performed for 6 h, both in the presence and in the absence of inhibitors of TLR4 (R. sphaeroides LPS, 20 μg/ml) and RAGE (blocking monoclonal antibody). Apoptosis at early and late stages was assessed by the annexin-V/PI staining using flow cytometry. Regulation of TNF-α and IL-10 gene expression was determined by RT-qPCR. PBMCs from diabetes patients tended to be more resistant apoptosis. There were no synergistic or antagonistic effects with the simultaneous activation of TLR4 and RAGE in PBMCs from either diabetes or non-diabetes group. Activation of TLR4 is more potent for the induction of TNF-α and IL-10; RAGE signalling had a negative regulatory effect on TNF-α expression induced by LPS. TLR and RAGE do not have relevant roles in apoptosis of PBMCs. The activation of TLR has greater role than RAGE in regulating the gene expression of IL-10 and TNF-α.